2020
DOI: 10.3390/pathogens9100804
|View full text |Cite
|
Sign up to set email alerts
|

The Host-Specific Intestinal Microbiota Composition Impacts Campylobacter coli Infection in a Clinical Mouse Model of Campylobacteriosis

Abstract: Human Campylobacter-infections are progressively rising globally. However, the molecular mechanisms underlying C. coli–host interactions are incompletely understood. In this study, we surveyed the impact of the host-specific intestinal microbiota composition during peroral C. coli infection applying an established murine campylobacteriosis model. Therefore, microbiota-depleted IL-10−/− mice were subjected to peroral fecal microbiota transplantation from murine versus human donors and infected with C. coli one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Previous studies also revealed that host susceptibility for and resistance against distinct enteropathogens including C. jejuni [49], Campylobacter coli [50], and Salmonella enterica [51] are determined by the host-specific intestinal microbiota. In order to elucidate the triangular relationship between enteropathogens on one side and immunity and the human gut microbiota on the other (host) side, we here tested carvacrol in IL-10 −/− mice harboring a human gut microbiota by subjecting secondary abiotic mice to oral transplantation of a fecal microbiota from human donors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also revealed that host susceptibility for and resistance against distinct enteropathogens including C. jejuni [49], Campylobacter coli [50], and Salmonella enterica [51] are determined by the host-specific intestinal microbiota. In order to elucidate the triangular relationship between enteropathogens on one side and immunity and the human gut microbiota on the other (host) side, we here tested carvacrol in IL-10 −/− mice harboring a human gut microbiota by subjecting secondary abiotic mice to oral transplantation of a fecal microbiota from human donors.…”
Section: Introductionmentioning
confidence: 99%
“…Such activation of macrophages with migration into the rectal epithelium was also observed in vivo in an ultrastructural analysis on Campylobacter spp.-infected patients with acute colitis [ 42 ]. Furthermore, in secondary abiotic IL-10 -/- mice challenged with human fecal microbiota, peroral C. coli infection promoted activation of macrophages in conjunction with the increased TNF-α secretion in colonic tissues 21 days post infection [ 43 ], a finding which supports the view of the immune activation being a central mechanism of the functional defects following the infection. In our present in vitro study, we also observed an activation of M1-macrophage-like THP-1 cells 48 h following C. concisus infection depicted through an increase in cell proliferation rate at different ranges of MOI from 25 up to 200 ( Figure S2B ).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies also revealed that the host-specific intestinal microbiota impacts the host's susceptibility to and resistance against distinct enteropathogens including C. jejuni , Campylobacter coli (Heimesaat et al, 2020), and Salmonella enterica (Chung et al, 2012). In order to elucidate the triangular relationship between enteropathogens on one side and the murine immunity and human gut microbiota on the other, the host side, we generated a human gut microbiota associated (hma) mouse model for C. jejuni induced inflammation.…”
Section: Introductionmentioning
confidence: 99%